Two-dimensional models of variable inertia from LiDAR data for structural analysis of timber trusses. (20th January 2020) - Hermida, J.; Cabaleiro, M.; Riveiro, B.; Caamaño, J.C.
Highlights: Historical wooden trusses are often composed of beam of irregular section. In many cases, the loads are also applied out of the nodes of the trusses. 2D model of variable inertia of wooden trusses with irregular sections from LiDAR data was developed. The developed algorithm is suitable for the modelling and subsequent structural analysis of trusses. The proposed method compared with other methods presents errors that do not exceed 8% in any case. Abstract: Historical wooden structures often present numerous irregularities and changes of section along the longitudinal axis of the beams that compose them. For this reason, in order to carry out a structural analysis, the creation of models that take into account the variation in the moment of inertia presented by each beam of the structure is fundamental. This geometrical characteristic is especially important in structures of timber beams and trusses when the loads are located out of the nodes. To achieve this aim, this work presents an algorithm that makes it possible to automatically carry out 2D models of variable inertia for the analysis of structures of beams from LiDAR data. The proposed methodology is based on the creation of beam elements of variable inertia, where the geometrical properties of each section of each beam and the general geometry of the structure are considered. The results obtained are very promising, presenting relative errors in the deformation analysis lower than 8% compared to other methods of classical modelling and a reduction of the processing time by more than 85%.